Breaking up and making up – reworking of Holocene calcarenite platform into rapidly‐forming beachrock breccias on a high energy coastline (St. Lucia, South Africa). Issue 3 (4th December 2021) - Falkenroth, Michaela; Green, Andrew N.; Cooper, J. Andrew G.; Menzel, Manuel D.; Hoffmann, Gösta
Abstract: Beachrocks are a common characteristic of tropical and subtropical coastlines. It is known that they have a substantial influence on beach morphodynamics and they are commonly utilised as indicators of palaeo‐sea levels. At the same time, facies variability in beachrocks is understudied and their effect on shoreline evolution is poorly understood. At Mission Rocks on the KwaZulu‐Natal coastline of South Africa a narrow beach with isolated sand patches occupies low points of an otherwise continuous 3 m thick, raised shore platform of sandy and gravelly beachrocks. These beachrocks are in the process of disintegrating into megagravel deposits through chemical and mechanical weathering in a wave‐dominated, high‐energy setting. The breakdown is potentially slowed by a contemporary, fast‐forming beachrock facies, that blankets the surface and fills fractures and potholes within the older platform. The accumulation and cementation of this recent beachrock is the focus of this study. The beachrock is dated by historical evidence to post‐World War II. Data from field observations, petrographic and geochemical methods reveal that the cementing agents of the beachrock were precipitated from marine water in a phreatic setting despite its position above the intertidal zone. Not only does this facies have implications for the interpretation of palaeo‐beachrock as a sea‐level indicator, it also raises further questions regarding modelling of coastal erosion of beaches associated with outcrops of beachrock.